Inferior Alveolar Nerve Lateralization and Transposition for Dental Implant Placement. Part I: a Systematic Review of Surgical Techniques - Boris Abayev; Gintaras Juodzbalys (Stilus Optimus, 2015)
Objectives: The purpose of this first part of a two-part series was to review the literature concerning the indications, contraindications, advantages, disadvantages and surgical techniques of the lateralization and transposition of the inferior alveolar nerve, followed by the placement of an implant in an edentulous atrophic posterior mandible. Material and Methods: A comprehensive review of the current literature was conducted according to the PRISMA guidelines by accessing the NCBI PubMed and PMC database, academic sites and books. The articles were searched from January 1997 to July 2014 and comprised English-language articles that included adult patients between 18 and 80 years old with minimal residual bone above the mandibular canal who had undergone inferior alveolar nerve (IAN) repositioning with a minimum 6 months of follow-up. Results: A total of 16 studies were included in this review. Nine were related to IAN transposition, 4 to IAN lateralization and 3 to both transposition and lateralization. Implant treatment results and complications were presented. Conclusions: Inferior alveolar nerve lateralization and transposition in combination with the installation of dental implants is sometimes the only possible procedure to help patients to obtain a fixed prosthesis, in edentulous atrophic posterior mandibles. With careful pre-operative surgical and prosthetic planning, imaging, and extremely precise surgical technique, this procedure can be successfully used for implant placement in edentulous posterior mandibular segments.